Physicochemical properties of Scaptotrigona mexicana honey from the Highlands of Veracruz, Mexico - López-Garay, Luz Anel; Trejo-Téllez, Libia Iris; Gómez-Merino, Fernando Carlos; Contreras-Oliva, Adriana; Pérez-Sato, Juan Antonio; Salinas-Ruiz, Josafhat (Ecosistemas y Recursos Agropecuarios, 2023)
Stingless bees play an important role in maintaining the balance of the ecosystems they inhabit by actively participating in the pollination of most flowering plants. The objective of this study was to characterize physicochemically honey from the stingless bee species Scaptotrigona mexicana from Fortín de las Flores, Cañada Blanca, and Manuel León, in Veracruz, Mexico, collected in 2017 and 2018. The experimental design was completely randomized, with two factors: location and year of sampling. The analysis of variance showed that the interaction of factors affected water activity, but not hydroxymethylfurfural content. In honey from Fortín de las Flores, greater values for color, electrical conductivity, pH, lactone acidity, and total acidity were observed. The year with the highest recorded values of the measured parameters was 2017. The data obtained indicate good quality of young honey and that the highest values of the measured variables were observed in Fortín de las Flores.